Experimentalismo y comunidad. Formas del afecto en Campo minado y Teatro de guerra de Lola Arias y Diarios del odio de Roberto Jacoby & Syd Krochmanly (Altre Modernità, 2022)
Based on the inquiry about community and affect, I propose a series of readings on recent Argentine projects, Diarios del odio by Roberto Jacoby & Syd Krochmalny, and Minefield/Campo minado and the film Teatro de guerra by Lola Arias. These projects allow to corroborate a creation of artificial communities as a form of aesthetic exploration around conflictives areas of politics and Argentine memory. Thereby, the question about the composition of a community is at the center of these assemblages that, by postponing the urgency of institutional requirements, give rise to various forms of experimentation, both in their constructive and conceptual forms. These modulations of high political conflict allow us to notice how community experimentation, together with the multiplicity of formats and supports, constitute these artistic projects as complex artifacts aimed at critically dismantling forms of contemporary violence.
Keywords: community; affect; experimentalism; violence; memory